On Germans & other Greeks : tragedy and ethical life - Schmidt, Dennis J. (Studies in Continental thought., 2001)
Tracing the efforts of philosophers to appropriate the issues opened up by tragedy as a literary form, Dennis Schmidt makes the argument that in the struggle to come to terms with the issues raised by tragedy, new and progressive avenues for addressing the questions of ethic life have come to the fore.